Phase transformations and control of residual stresses in thick spray-formed steel shells - Rayment, T; Hoile, S; Grant, P (2004)
Large, thick steel shells for tooling applications have been produced using a robot manipulated electric arc spraying technique with steady-state temperatures ranging from 170°C to 450°C. Critical to these experiments has been the use of a real-time feedback control system for surface temperature based on infrared thermal imaging. There was a reproducible trend in net residual shell distortion as a function of temperature with residual tensile stresses in the shell for temperatures ≤210°C and ≥390°C, and net compressive stresses at intermediate temperatures. In-situ linear displacement sensor experiments have been used to investigate the dynamic distortion of sprayed steel shells on steel substrates, over the same range of surface temperatures. Residual and in-situ distortion measurements confirmed two manufacturing temperatures at which stresses in the steel shells were either minimized or eliminated. A numerical model has been developed to relate shell quench and transformations stresses to the shell dynamic distortion behavior. It is proposed that tensile quench stresses are balanced by the time- and temperature-dependent expansive austenite-to-bainite phase transformation.